Clustered tree size analysis of bio-productivity of Dinghushan National Nature Reserve in China - Li, Yuelin; Nyongesah, Maina John; Deng, Libin; Haider, Fasih Ullah; Liu, Shizhong; Mwangi, Brian Njoroge; Zhang, Qianmei; Chu, Guowei; Zhang, Deqiang; Liu, Juxiu; Meng, Ze (Frontiers in Ecology and Evolution, 2023)
Over various terrain types, natural forests exhibit tree size and biomass variation. We started long- term research that consists of forest vegetation surveys in the Dinghushan National Nature Reserve to comprehensively investigate productivity based on the structure and species composition of China’s forest communities. We grouped the trees into three categories, i.e., as large or mature (DBH > 30 cm), medium-sized or growing (DBH 10–30 cm), and small-sized or regenerating seedlings (DBH < 10 cm). Forest data observations, i.e., species DBH, height, and biomass components (trunk, leaves, branches, above-ground dry weight, and below-ground dry weight) were recorded by use of standard protocols. All recorded observations were statistically analyzed by use of SPSS version 25. To comprehend the connections between the many elements of forest bio-productivity, linear regression analysis was utilized. Total above-ground biomass was 34.19 ± 5.75Kg/tree, but varied results were obtained when the forest was clustered based on DBH. Large-sized trees contributed an average of 2400.54 ± 510.4 kg/tree (93.24%), while medium-sized trees contributed 171.61 ± 25.06 kg/tree, and the least was regenerating seedlings which contributed 3.013 ± 0.07 kg/tree. There were positive linear relationships for all life forms between biomass and DHB, as well as DBH and height. The evergreen broadleaved shrubs were shorter in height (3.06 ± 0.99 m) than palm-leaved life forms (19.29 ± 5.39 m). Height influenced biomass accumulation and hence C gain, where life forms with tall stands had higher biomass. Generalized biomass estimation without clustering based on life forms or size class underestimates biomass components and hence lower C stocks for most forests worldwide. It’s also crucial to remember that trees with big DBH have tall, broad, well-lit crowns, which raise the primary productivity of forests and increase carbon storage. Besides natural disturbance (Typhoon) and climate change, it could be interesting to understand the relationship between soil resources such as nutrient and soil moisture content. These are factors that have direct impact on growth and biomass accumulation.